2020
DOI: 10.5114/hm.2021.100014
|View full text |Cite
|
Sign up to set email alerts
|

Are vertical jump height and power output correlated to physical performance in different sports? An allometric approach

Abstract: PurposeThis study aimed to analyse the relationship between vertical jump parameters – jump height (JH), peak power output (PPO), and mean power output (MPO) – and specific physical performance in different sports using the allometric approach. In this sense, it was verified whether scaled power output for body mass might have a stronger correlation with physical performance than raw power output.MethodsThe study involved 52 male athletes (21 judokas, 18 futsal players, and 13 sprint runners). They performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Assessments of lower body explosive strength in young Brazilian athletes (sprint running, judo and futsal) indicate medium and strong associations of vertical jump and muscle power values with physical performance in sport-specific tests, so explosive strength is a parameter that signals and influences sports performance. The highest values for vertical jumps are achieved by sprinters, then futsal players and judo athletes [39]. Variations in muscle strength and power are identified between male judo and Brazilian jiu-jitsu practitioners (19-26 years old).…”
Section: Variations Of Explosive Strength Depending On the Level And ...mentioning
confidence: 90%
“…Assessments of lower body explosive strength in young Brazilian athletes (sprint running, judo and futsal) indicate medium and strong associations of vertical jump and muscle power values with physical performance in sport-specific tests, so explosive strength is a parameter that signals and influences sports performance. The highest values for vertical jumps are achieved by sprinters, then futsal players and judo athletes [39]. Variations in muscle strength and power are identified between male judo and Brazilian jiu-jitsu practitioners (19-26 years old).…”
Section: Variations Of Explosive Strength Depending On the Level And ...mentioning
confidence: 90%
“…Jump height (JH) is one of the most reliable and informative assessments associated with muscle power, a crucial factor in sports performance 1 , 2 . Therefore, JH measurements are widely utilized in various sports disciplines for training process monitoring, with JH improvement also developed as an independent skill 1 , 3 . A study by Pedersen et al 4 showed a strong relationship between JH and physical match performance in high-level female football players.…”
Section: Introductionmentioning
confidence: 99%
“…The jumping ability of an individual is a predictor for performance in various types of sports in elite and recreational athletes [1][2][3], including sprint performance [4]. Besides sports performance, the ability to jump was shown to be a predictor for functional capacity [5] and the risk of falling [6].…”
Section: Introductionmentioning
confidence: 99%